ASSESSING THE INFLUENCE OF SPORTS PARTICIPATION ON ACADEMIC PERFORMANCE AND TIME MANAGEMENT SKILLS AMONG NON-SPORTS STUDENTS IN COLLEGES - Malhotra, Himani (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Junk food is defined as the food which is less in nutritional value and high in calories, sugar, fat and salt. It has a harmful effect on health and mental well-being therefore the purpose of the present study has been, to assess the knowledge, attitudes and practices of non-sports college students of Delhi University regarding the high consumption of junk food. A total of maximum fifty non-sports college students-male and female of 18-20 years of Delhi University from different colleges and academic disciplines such as Bachelors & Masters, has been randomly selected. To collect the quantitative data, the survey questionnaire has been developed and administered to the selected non-sports college students as per their feasibility and convenience. Based on the findings, majority of students emphasized various factors for consuming the junk food: 1) taste and cravings, 2) Due to busy schedule and long working hours spent in college for studies and various activities and living outside home, lack of facilities of cooking, students are bound to have junk food, 3) Availability of junk food options on campus that impact students’ dietary practices and lack of healthier alternatives, 4) Peer influence, 5) Marketing Strategies. It is concluded that more awareness, valuable insights and facilities to youth about potential health risk of junk food, should be provided. Formal education/guidance should be given on healthy eating habits that motivate themselves to prepare instant tastier healthy food. They should be informed of various initiatives/campaigns promoting healthy eating habits at their college. Seminars, workshops or educational programs promoting healthy eating habits and reducing junk food consumption, should be organized for students at their colleges.